Implementation Of A Website-Based Recording And Reporting System For Mosque Construction Donations - Rurianto; Yuniar Laeli Nur Faizah; Purwanto (CV.RIZANIA MEDIA PRATAMA, 2025)
Managing donation funds requires transparency and accountability to maintain trust and ensure proper use of funds. This study aims to implement a web-based fund recording and reporting information system to assist in the efficient and transparent financial management of the Al-Ikhlas Mosque. The problems faced by the Al-Ikhlas Mosque management include manual recording that is prone to loss, miscalculations, and a lack of transparency to residents. To address these issues, a